2022
DOI: 10.1212/wnl.0000000000200884
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Accelerometer-Derived Physical Activity Measurements and Brain Structure

Abstract: Background and Objectives:While there is growing evidence that physical activity promotes neuronal health, studies examining the relation between physical activity and brain morphology remain inconclusive. We therefore examined whether objectively-quantified physical activity is related to brain volume, cortical thickness and grey matter density in a large cohort study. Additionally, we assessed molecular pathways that may underlie the effects of physical activity on brain morphology.Methods:We used cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…Gene enrichment analysis of the nearest genes across the CpG sites demonstrated that genes, whose methylation levels were most strongly associated with physical activity, were enriched in pathways related to regulation of vascular endothelial function as well as pathways related to nervous system function and health (including synaptic signalling, sensory development and perception, as well as cell proliferation and interaction). These results thus suggest that physical activity may particularly affect neuronal signalling, thereby pointing to a novel molecular basis for previous findings suggesting that physical activity is beneficial for brain function (Silverman & Deuster, 2014;World Health Organization, 2020), an effect that is particularly evident in brain regions with a high oxidative demand (Fox et al, 2022). Larger EWAS of physical activity are required for the identification of additional molecular mechanisms through which physical activity exerts its beneficial health effects.…”
Section: Ta B L E 4 (Continued)mentioning
confidence: 64%
“…Gene enrichment analysis of the nearest genes across the CpG sites demonstrated that genes, whose methylation levels were most strongly associated with physical activity, were enriched in pathways related to regulation of vascular endothelial function as well as pathways related to nervous system function and health (including synaptic signalling, sensory development and perception, as well as cell proliferation and interaction). These results thus suggest that physical activity may particularly affect neuronal signalling, thereby pointing to a novel molecular basis for previous findings suggesting that physical activity is beneficial for brain function (Silverman & Deuster, 2014;World Health Organization, 2020), an effect that is particularly evident in brain regions with a high oxidative demand (Fox et al, 2022). Larger EWAS of physical activity are required for the identification of additional molecular mechanisms through which physical activity exerts its beneficial health effects.…”
Section: Ta B L E 4 (Continued)mentioning
confidence: 64%
“…This study used cross-sectional baseline data from the first 3000 participants (age range: 30–95 years ( n = 50–95 years) of the Rhineland Study, an ongoing population-based cohort study in Bonn, Germany ( 23 ). Participants were recruited from March 2016 to March 2019.…”
Section: Methodsmentioning
confidence: 99%
“…Physical activity was continuously recorded with activPAL3 accelerometers across 7 days. We calculated average daily energy expenditure (in metabolic equivalent hours, MET hours) weighted by sensor wear time as described previously (23).…”
Section: Assessment Of Covariatesmentioning
confidence: 99%
“…Although the study by Fox et al 3 contributes to our understanding of the neuroprotective effects of physical activity, it has some limitations. Its cross-sectional design precludes conclusions about causality.…”
mentioning
confidence: 99%
“…Findings examining the associations between physical activity and exercise interventions on brain volume change in older adults have largely been mixed, 6,7 likely owing to the inability to disentangle distinct components of physical activity because of limited power and little uniformity in the regions of interest examined. The study by Fox et al 3 found a preferential impact of physical activity on motor regions, which are often not explored in research on brain health.…”
mentioning
confidence: 99%